2018
DOI: 10.1051/e3sconf/20184301008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Natural Zeolite and Chicken Manure Derived Biochar for Carbon Dioxide Adsorption in Biogas

Abstract: Although biogas is clean and environmentally friendly, its existence is often unsustainable, especially in rural area. Consumption of fossil fuel energy still dominates because cheaper, higher in energy efficiency and ready to use than biogas. One of the efforts to make biogas can compete with fossil fuel energy is by increasing calorific value. Reduction of carbon dioxide by adsorption enhances the calorific value that evidenced by methane enrichment. In this study, we investigated the effect three types of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…This will result in the increase of the contact area between the CO 2 gas and the adsorbent, so the CO 2 content will continue to decrease along with the increase in the mass of the adsorbent. These results are in line with previous studies [17], [18], [19], [20]. Analysis of the biogas flowrates effect on CO 2 concentrations in biogas with mass and time variables can be seen in Figure 5.…”
Section: Results and Discussion Co 2 Concentrationsupporting
confidence: 92%
See 2 more Smart Citations
“…This will result in the increase of the contact area between the CO 2 gas and the adsorbent, so the CO 2 content will continue to decrease along with the increase in the mass of the adsorbent. These results are in line with previous studies [17], [18], [19], [20]. Analysis of the biogas flowrates effect on CO 2 concentrations in biogas with mass and time variables can be seen in Figure 5.…”
Section: Results and Discussion Co 2 Concentrationsupporting
confidence: 92%
“…High level (+1) shows high treatment value and low level (-1) shows low treatment value on each factor [15]. The matrix form is obtained in Figure 8; Method of the Gauss Siedel iteration was used the completion of matrix on Figure 8 [17], [19], [20]. Increasing the mass of the adsorbent will increase the percentage of CH 4 because a lot of CO 2 is bound to the adsorbent, thereby increasing the ratio between CH 4 and CO 2 .…”
Section: Ch 4 Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Khalil and Auora [4] reported that biochar can exhibit selective adsorption of carbon dioxide. The combination of natural zeolite and chicken manure-based-biochar is able to adsorb carbon dioxide and increase methane content of biogas by approximately 29% compared to non-purified biogas [9]. This study investigates the use of rice husk-based biochar for biogas purification that is considered rare.…”
Section: Introductionmentioning
confidence: 99%